Frailty and healthcare costs: longitudinal results of a prospective cohort study - Hajek, André; Saum, Kai-Uwe; Brenner, Hermann; Haefeli, Walter E. (Age & ageing, 2018)
Objectiveto investigate how frailty and frailty symptoms affect healthcare costs in older age longitudinally.Methodsdata were gathered from a prospective cohort study in Saarland, Germany (two waves with 3-year interval, n = 1,636 aged 57-84 years at baseline). Frailty was assessed by the five Fried frailty criteria. Frailty was defined as having at least three criteria, the presence of 1-2 criteria as ‘pre-frail’. Healthcare costs were quantified based on self-reported healthcare use in the sectors of inpatient treatment, outpatient treatment, professional nursing care and informal care as well as the provision of pharmaceuticals, medical supplies and dental prostheses.Resultswhile the onset of pre-frailty did not increase (log) total healthcare costs after adjusting for potential confounders including comorbidity, progression from non-frailty to frailty was associated with an increase in total healthcare costs (for example, costs increased by ~54 and 101% if 3 and 4 or 5 symptoms were present, respectively). This association of frailty onset with increased healthcare costs was in particular observed in the inpatient sector and for informal nursing care. Among the frailty symptoms, the onset of exhaustion was associated with an increase in total healthcare costs, whereas changes in slowness, weakness, weight loss and low-physical activity were not significantly associated with an increase in total healthcare costs.Conclusionsour data stress the economic relevance of frailty in late life. Postponing or reducing frailty might be fruitful in order to reduce healthcare costs.
Article was published electronically on 21 September 2017
Gesehen am 19.03.2018